Analisis Kesulitan Belajar Siswa Kelas II Pada Materi Penjumlahan Dan Pengurangan Bilangan - Alan Suherdi; Aliyudi Aliyudi; Yandi Aryanti (Departement of Mathematics Education, 2020)
Mathematics is usually considered by students as the most difficult subject, this is a problem for teachers so there is a need for innovation in the learning process so that students' assumptions can be resolved.Mathematics can also be used to analyze and simplify as problems. Integers are numbers consisting of counts and negative numbers, the set of all integers denoted by Z, the set Z is closed to addition operations, subtraction operations and multiplication operations. This research method is qualitative. The study population is class II MI BAABUSSALAAM. The sample was taken in only one class with 20 students. Data collection was carried out with two forms of written test instruments in the description and interviews of students who experienced types of mathematical problem solving difficulties namely 1) understanding the problem 2) making plans 3) implementing the plan, 4) looking back at the results obtained. Data analysis was performed by examining the number of answers based on grade level, namely upper class, lower class and middle class supported by interview test results. We can apply the correct concepts regarding integer material to students who have difficulty.